2015
DOI: 10.1002/ajim.22436
|View full text |Cite
|
Sign up to set email alerts
|

How to engage small retail businesses in workplace violence prevention: Perspectives from small businesses and influential organizations

Abstract: Dissemination of WVPPs to small businesses may require models inclusive of influential individuals (e.g., respected business owners) as intermediaries to reach small businesses with few formal connections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The use of intermediaries has been proposed as a potentially effective way of reinforcing messages and reaching small business employers, and doing so through a trusted or at least a potentially acceptable source that a small businesses recipient might listen to. In previous work, we, and others, have described models for using intermediaries to reach SMEs (Hasle and Limborg, 2006; Hasle et al, 2011; Sinclair et al, 2013; Bruening et al, 2015; Cunningham and Sinclair 2015; Okun et al, 2017) (Fig. 2).…”
Section: Communication Channel Researchmentioning
confidence: 99%
“…The use of intermediaries has been proposed as a potentially effective way of reinforcing messages and reaching small business employers, and doing so through a trusted or at least a potentially acceptable source that a small businesses recipient might listen to. In previous work, we, and others, have described models for using intermediaries to reach SMEs (Hasle and Limborg, 2006; Hasle et al, 2011; Sinclair et al, 2013; Bruening et al, 2015; Cunningham and Sinclair 2015; Okun et al, 2017) (Fig. 2).…”
Section: Communication Channel Researchmentioning
confidence: 99%
“…Insurance providers, equipment suppliers, trade associations, professional and technical associations, and government agencies were all reported as sources of safety information by more than one third of smaller business respondents. The need to channel OSH assistance diffusion efforts through intermediary organizations (organizations that are already well-connected to small business networks) has been well-documented in the OSH literature as a promising approach to improving OSH among small firms [Hasle et al, 2009; Olsen et al, 2012; Sinclair et al, 2013; Cunningham and Sinclair, 2015; Bruening et al, 2015]. As suggested by the survey data reported here certain organizational membership organizations (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…The difference in results between the website visits and interviews suggests that there are other significant barriers aside from awareness of the availability of information that prevent small business owners from actively seeking OSH information. Although the specific barriers for the recipients of the postcards are currently unknown, literature on OSH in small businesses suggests that factors such as lack of resources and production pressures are often encountered in small businesses (Bruening et al, 2015; Olsen et al, 2012; Brosseau and Li, 2005; Parker et al, 2012; Masi and Cagno, 2015). Additional barriers may be that small businesses would prefer receiving safety information in a method other than an online source, or simply would prefer an easier way to reach online safety information, such as a barcode which could be scanned by a mobile device.…”
Section: Discussionmentioning
confidence: 99%
“…Given that outreach to small businesses is difficult, especially when they are not members of a trade association or larger organization, it has been suggested that partnerships with influential individuals or groups can aid diffusion of OSH information (Bruening et al, 2015; Hasle and Limborg, 2006; Sinclair et al, 2013). Researchers from the National Institute for Occupational Safety and Health (NIOSH) developed a diffusion model for small businesses in which an initiating organization (often a governmental public health/safety organization) works with an intermediary organization to transmit OSH information to small businesses (Sinclair et al, 2013).…”
Section: Introductionmentioning
confidence: 99%